2011
DOI: 10.1044/1059-0889(2011/10-0035)
|View full text |Cite
|
Sign up to set email alerts
|

Ear Asymmetries and Asymmetric Directional Microphone Hearing Aid Fittings

Abstract: An asymmetry between ears for speech understanding in noise did not result in preference for 1 asymmetric fitting over the other in everyday listening situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…To date asymmetric directivity has only been suggested in bilateral HA-users as a permanent setting instead of manually switching between directional modes [ 41 , 65 ]. According to the “better SNR ear” principle, the effective SNR should be at least as good as the better of the two ears [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date asymmetric directivity has only been suggested in bilateral HA-users as a permanent setting instead of manually switching between directional modes [ 41 , 65 ]. According to the “better SNR ear” principle, the effective SNR should be at least as good as the better of the two ears [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the “better SNR ear” principle, the effective SNR should be at least as good as the better of the two ears [ 66 ]. But the reported difference between asymmetric and symmetric directivity varies across HA-studies, ranging from no difference [ 41 , 65 , 67 , 68 ] to a significant benefit in favor of the symmetric configuration [ 30 , 59 , 60 ]. However, CI-recipients are a different population, especially in the event of bimodal fitting.…”
Section: Discussionmentioning
confidence: 99%
“…If the LDN SNR and RDN SNR are equivalent or the direction of the estimated DN is 180°, the device positioned on the most HI ear is set to OM mode, and the contralateral device is set to DM mode, following a study by Cord et al. that demonstrated that for subjects with asymmetric hearing ability, providing directional processing to the ear with better hearing‐in‐noise ability yielded significantly better performance and providing directional processing to the ear with poorer hearing‐in‐noise ability did not yield a significant directional advantage. For the DM‐mode device, the output of the beamformer is regarded as the input signal, and for the OM‐mode device, the unprocessed input signal of a front microphone is regarded as the input signal.…”
Section: Methodsmentioning
confidence: 99%
“…In monaurally HI persons, who have hearing loss in only one ear, the ear with normal hearing can be used for the detection of such informative ambient sounds; however, in binaurally HI persons who use independently operated, forward‐focusing HS devices in both ears, most ambient sounds not in front of the person may be attenuated. Therefore, in order to provide a more natural ambient sound to binaurally HI persons without increasing the interference of ambient noises, several groups have suggested the concept of an asymmetric directional microphone (DM) algorithm, which applies the forward‐focusing beamformer to one ear and an omnidirectional microphone (OM) algorithm to the other ear simultaneously . However, in most conventional bilateral asymmetric DM algorithms, two HS devices are operated independently, and therefore, several limitations exist: (i) the direction of the most dominant noise source (DN) around the listener cannot be determined because comparison between the two devices is not available; and (ii) when the DN moves near the OM‐mode device, the roles of the DM‐mode and OM‐mode devices cannot be switched automatically to minimize the interference of the DN.…”
mentioning
confidence: 99%
“…However, for noisy scenarios with the sound source coming from the side, one or two omnidirectional microphones work better compared to binaural directional microphones (Hornsby and Ricketts 2007;Kuk et al 2005;Wu et al 2013). Some hearing aids now allow for switching to an asymmetric microphone setting when speech is detected to the side or back of the listener (Nyffeler 2010;Cord et al 2011). However, asymmetric hearing aid processing can be confusing for hearing aid users for the purposes of localisation (Ibrahim et al 2013), which is essential for safe walking (Campos, Ramkhalawansingh, and Pichora-Fuller 2018).…”
Section: Introductionmentioning
confidence: 99%